Dampak Perubahan Iklim Terhadap Produktivitas Ternak Dan Strategi Adaptasi Peternak - Rusdan (Jurnal Ilmu Peternakan Indonesia, 2025)
Climate change poses a significant challenge to the livestock sector, particularly affecting livestock productivity and farmers’ livelihoods. This study aims to analyze the impact of climate change on livestock productivity and to identify adaptation strategies implemented by farmers across regions with different climatic characteristics. A mixed-methods approach was employed, combining quantitative data from surveys of 150 farmers and qualitative data from in-depth interviews and focus group discussions. Results indicate a significant decline in milk production, body weight gain, and an increase in livestock disease incidence associated with rising temperatures and changing rainfall patterns. Farmers have responded by adopting various adaptation strategies, including improved barn management, selection of heat-tolerant livestock breeds, and supplementary feeding practices. This study highlights the importance of policy support and technology access to strengthen farmers’ resilience against climate change. The findings provide valuable insights for developing sustainable livestock adaptation policies and programs.